1962
DOI: 10.1042/bj0840390
|View full text |Cite
|
Sign up to set email alerts
|

The influence of structure on the hydrolysis of substituted phenyl α-d-glucosides by α-glucosidase

Abstract: Nath & Rydon (1954) investigated the influence of structure on the hydrolysis of some substituted phenyl P-D-glucosides by ,B-glucosidase, correlating measured values of the kinetic constants for the enzymic hydrolysis, based on the classical theory of Michaelis & Menten (1913), with the substituent constants (Hammett, 1940), a, for the substituents in the phenyl group. The present paper describes a similar study of the hydrolysis of some substituted phenyl OC-D-glucosides by the a-glucosidase of brewer's yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The results with aryl glucosides show no systematic dependence of either logkca1. or log (kcat./Km) on the pKa of the departing phenol, correlation coefficients of 0.62 and 0.19 respectively being obtained; the five data points are adequate to confirm that the random variation of kinetic parameters with substrate structure observed with ten substrates by Hall et al (1962) was not a consequence of catalysis by several isoenzymes not separable by the techniques of the time.…”
Section: Resultsmentioning
confidence: 66%
“…The results with aryl glucosides show no systematic dependence of either logkca1. or log (kcat./Km) on the pKa of the departing phenol, correlation coefficients of 0.62 and 0.19 respectively being obtained; the five data points are adequate to confirm that the random variation of kinetic parameters with substrate structure observed with ten substrates by Hall et al (1962) was not a consequence of catalysis by several isoenzymes not separable by the techniques of the time.…”
Section: Resultsmentioning
confidence: 66%
“…with aglycone acidity, and Dahlquist et al (1969) have found an a-deuterium kinetic isotope effect (kHIkD) of 1.01±0.01 for the hydrolysis of phenyl ,B-D-glucopyranoside by this enzyme. Poor Hammett correlations have, however, also been found for brewer's yeast a-glucosidase (Hall et al, 1962), a-maltosidase (Suetsugu et al, 1971), mammalian ,B-glucuronidase (Watanabe & Suzuki, 1970;Wang & Touster, 1972), and fungal ,B-xylosidase (van Wijnendaele & De Bruyne, 1970).…”
Section: (A) Rmentioning
confidence: 99%
“…The use of pNPG as a substrate for α-glucosidase activity assays began in the 1950s and mainly focused on yeast glycosidases (Hall et al, 1962;Robertson & Halvorson, 1957). Later, this method was adapted to measure the inhibitory properties of polyphenols on αglucosidase in vitro because the method is convenient and the pNG that is a product of enzymatic decomposition of pNPG has a large range of linear relationship between the concentration and absorbances (Ambreen et al, 2020).…”
Section: Comparison Between the Traditional And Improved Methods For α-Glucosidase Inhibition Assaymentioning
confidence: 99%